ANALISIS PENGARUH KESEJAHTERAAN KARYAWAN TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. ASURANSI JIWASRAYA (PERSERO) MEDAN - Purba, Betniar (UNIKA Santo Thomas, 2018)
The purpose of this study was to determine and analyze the influence of employee welfare on employee morale at PT. Asuransi Jiwasraya (Persero) Medan, for the development of science, especially in the field of human resource management, as a reference in conducting further research. The total sample of the study was all members of the population of 30 people. The type of data used are primary and secondary data, data analysis methods are used simple linear regression analysis. From the results of the research and discussion, the tcount is 7.767 with a significance level of 0.000, so H1 is accepted and H0 is rejected. That is, employee welfare has a significant effect on employee morale at PT. Jiwasraya Insurance (Persero) Medan, can be received at a 5 percent significance level. The simple linear regression equation obtained is Y = 0.773 + 0.696X. That is, employee welfare has a positive effect on employee morale at PT. Jiwasraya Insurance (Persero) Medan. This can be seen from the regression coefficient which is positive. The value of the correlation coefficient (R) is 0.826, meaning that employee welfare has a strong relationship with employee morale at PT. Jiwasraya Insurance (Persero) Medan. The determinant coefficient value (R Square) is 0.683, meaning that employee morale can be explained by employee welfare of 68.3% while 31.7% is explained by other factors such as promotion and incentive. Suggestions given as material for consideration to the leadership of the company is to increase employee morale, the company should pay attention to the welfare of employees by providing official housing facilities and increase family benefits to employees. It is better for the company to increase employee morale by giving awards to the best performing employees, such as promotion and incentives.